The 'one and a half round microcatheterization technique' for stent-assisted coil embolization of intracranial aneurysm: technical case series. (30th May 2013) - Miyachi, Shigeru; Matsubara, Noriaki; Izumi, Takashi; Asai, Takumi; Yamanouchi, Takashi; Ota, Keisuke; Oda, Keiko; Wakabayashi, Toshihiko
Abstract : Background: Stent-assisted coil embolization is useful for wide-necked, large and giant aneurysms, and is effective for avoiding coil herniation. However, the mobility of the microcatheter is often restricted, resulting in deviated or unbalanced coiling. In order to prevent this insufficient coiling, the authors devised a method for microcatheterization, the 'one and a half round microcatheterization technique'. This technique is based on the formation of a one and a half round loop by the microcatheter along the aneurysmal wall. Furthermore, this technique can be supplemented with the double-catheter technique. Methods: From July 2010 to July 2012, the authors used this technique for 20 aneurysms in 20 patients (6 men and 14 women; mean age 61.7 years). The one and a half round microcatheterization technique was used alone in 12 cases and was supplemented with the double-catheter technique in eight. The clinical and angiographic results were retrospectively evaluated. Results: The average aneurysm size was 16.7 mm; 12 aneurysms (60%) were located at the internal carotid artery, 5 (25%) at the basilar artery and 3 (15%) at the vertebral artery. Immediate angiographic results showed complete obliteration in 6 aneurysms (30%) and residual neck in 10 (50%), leaving 4 residual aneurysms (20%). This technique was useful and acceptably safe for packing the aneurysmal sac entirely. During an average follow-up of 20.5 months, 13 of the 18 aneurysms (72%) were stable or had improved, although 3 (16%) required retreatment. Conclusions: The one and a half round microcatheterization technique provides dense coil packing for stent-assisted embolization of large or giant aneurysms.